Produksi ASI Ibu Nifas Pasca Mendengarkan Surat Ar-Rahman - Nurmisih Nurmisih; Lia Artikasari; Dwi Yuliani Sentosa; Enny Susilawati (STIKes Hang Tuah Pekanbaru, 2022)
The recitation of the Qur'an contains the element of the human voice, which is a wonderful healing tool and the most accessible tool. Ar-Rahman means the Most Gracious. All verses in Surah Ar-Rahman have short verse characters so that they are comfortable to listen to and can provide a relaxing effect for the listener. This study was a pre-experimental study with one group pretest-posttest to determine the effect of listening to Surah Ar-Rahman's on breast milk production in postpartum mothers at Putri Ayu Health Center Jambi City. This research was conducted from January to July 2019 at the Putri Ayu Health Center, Jambi City. The population in this study was the target of postpartum mothers at the Putri Ayu Health Center in 2019 which amounted to 859 people. The sample in this study was taken by the purposive sampling technique. The research data used a questionnaire to determine the amount of breast milk production in postpartum mothers. The data collected were analyzed by univariate and bivariate. The results showed that the production of breast milk in postpartum mothers before being given Surah Ar-Rahman was in the fairly smooth category, namely as many as 24 respondents (57.1%) and before being given Ar-Rahman's letter in the current category, namely 37 respondents (88.1%). The results of the analysis show that there is an effect of listening to Surah Ar-Rahman on the production of breast milk in postpartum mothers at the Putri Ayu Health Center, Jambi City in 2019 with a p-value = 0.000. It is recommended that the results of this study can be used as input for health workers, especially midwives, so that they can provide innovations and interventions in increasing breast milk production for mothers, one of which is by using Surah Ar-Rahman.